Interactive learning : the art and science of teaching - STEINAKER, Norman W.; Lorraine S. Leavitt (Dubugue,IA : Kendall Hunt publishing, 2010)
Educators across content areas have turned to Classroom Strategies for Interactive Learning for almost two decades. This fully updated fourth edition delivers rich, practical, research-based strategies that readers have found invaluable in the context of today's classrooms. Doug has written all-new chapters that focus on the instructional shifts taking place as the Common Core State Standards are implemented across the United States.
Includes bibliography and index